2015
DOI: 10.1111/jnc.13089
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of the miR‐200 family in regulating differentiation and proliferation of neurons

Abstract: The generation of differentiated and functional neurons is a complex process, which requires coordinated expression of several proteins and microRNAs (miRNAs). The present study using nerve growth factor (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 46 publications
1
59
0
Order By: Relevance
“…Table 1 summarizes the results of a myriad of studies, which suggest that miR-200 members play a critical role in the differentiation and proliferation of neurons [8,9,10], podocyte differentiation [11], taste bud formation [12], insulin signaling pathway regulation in the control of fat body and body size [7], and for the hormonal regulation of endometrial stromal decidualization [13,14] during embryo implantation [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Table 1 summarizes the results of a myriad of studies, which suggest that miR-200 members play a critical role in the differentiation and proliferation of neurons [8,9,10], podocyte differentiation [11], taste bud formation [12], insulin signaling pathway regulation in the control of fat body and body size [7], and for the hormonal regulation of endometrial stromal decidualization [13,14] during embryo implantation [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Among them, miR-200a/b/c, miR-141, and miR-429 in the miR-200 family were significantly upregulated in early age AD in mice. In nerve system, miR-200 family is enriched in olfactory and has been implicated in neuronal proliferation and differentiation (Choi et al, 2008; Pandey et al, 2015). Phosphatase and tensin homolog deleted on chromosome 10 (PTEN), a famous tumor suppressor, was found to play important roles in neurogenesis, neurite outgrowth and synaptic plasticity (Zhou and Parada, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that many genes are involved in regulating the proliferation and differentiation of NSCs/NPCs. Among these genes, Hook3, DOCK7, Axin, Smek1 and some known microRNAs have all been shown to play important roles in regulating MT activities and also to be involved in neurogenesis [3236]. However, how does Kif2a, as a MT-depolymerizing protein, regulate embryonic neocortical neurogenesis?…”
Section: Discussionmentioning
confidence: 99%